Penyuluhan Pengetahuan Bahaya merokok pada Remaja di Desa Doda Kecamatan Kinovari Kabupaten Sigi Sulawesi Tengah - HS, Mutmainnah.; Mua, Estelle Lilian; Sepang, Janice; Beba, Nova Natalia; Susanto, Denny; Ribka, Juliana Neng; Sabarulin, Sabarulin; Jumain, Jumain; Madude, Meilin Anggreyni; Purwaningsih, Sri; Restawan, I Gede; Assa, Anggri Alfira Yunita (Jurnal Abdimas Kesehatan (JAK), 2024)
Adolescence according to WHO is the phase between childhood and adulthood in the age range between 10 to 19 years. The world's youth age group is 1.2 billion or 18% of the world's population. Cigarettes and tobacco products consumed by humans are generally are plant leaves (Nicotina, tabacum, nicotina rustica, and other species) that are burned, smoked, inhaled or chewed. There is 2550, a chemical in processed tobacco leaves. Some chemicals quickly cause health problems, lung damage, and weakening of stamina, if burnt cigarette smoke contains about 4000 chemicals, 43 of which are toxic such as nicotine such as nicotine (pesticide), CO (toxic gas), tar. The high prevalence of smokers in Indonesia will increase the risk of these diseases which threaten not only active smokers but also smokers. In active smokers, the danger threatens all organs of the body with impaired function to cancer such as those of the heart and blood vessels (coronary heart disease and blood vessels), respiratory tract (COPD, asthma and nasopharyngeal cancer), and disorders of the reproductive system and pregnancy (disability fetuses, miscarriages, pelvic infections and cancer in the organs of passive smoking adults and children). Users of tobacco products are decreasing, the number of teenagers aged 13-15 who smoke cigarettes has increased in 2014 (18.3%), 2019 (18.8% ). The method used is face-to-face through counseling and using questionnaires, the application of education in the health sector. The results of health education activities through this training are that there is an increase in knowledge about the dangers of smoking by 70% and 70% of adolescents wish to stop smoking